Research of the Traction Control of Heavy Type Construction Vehicle on Complex Road Surface - Yu Rui; Xia Xiaohui (Jixie chuandong)
For the problems of heavy type construction vehicle change greatly work condition and the poor driving characteristics in the process of driving,through the introduction of the engine throttle and brake torque control in the vehicle,the heavy type construction vehicle mathematical model is established,a comprehensive control strategy for complex road surface condition of heavy construction vehicle traction is put forward.